Greece: solidarity and adjustment in times of crisis - Giannitsis, Tassos; Zografakis, Stavros (Düsseldorf, 2015)
"This report attempts to examine the impact of the crisis and crisis policies on incomes, inequality and poverty in Greece. Based on extensive income and tax data, it investigates changes in incomes, direct, indirect and property taxation and their incidence between 2008 and 2012-13, their impact on pre- and post-tax inequality and the resulting social reclassifications within the Greek society. The report is distinguishing income by sources at the deciles level, including the top 1% and 0.1%, household and individual income while focusing also on the sub-groups of the 'same households' and the 'same individuals'. Furthermore, the analysis combines unemployment and income data and uses an 'index of despair' reflecting the pressure felt by households hit from salary drop and unemployment. The findings suggest that pauperisation hit large parts of the society, that policies had very differentiated effects on different groups and that, therefore, average values obscure contrasting changes in inequality regarding particular sub-groups, that during the crisis all income classes comprise winners and losers and last, but not least, that many macro-variables and social indicators were the result of a deficient crisis management approach and ideological inflexibility coupled to established political interests, making the exit from the crisis more complicated and painful. The findings of this analysis should be assessed in the light of the severe economic depression caused by the Troika's policies."